PENGARUH ENDORPHINE MASSAGE TERHADAP SKALA INTENSITAS NYERI KALA I FASE AKTIF PERSALINAN - Antik Antik; Arum Lusiana; Esti Handayani (JURNAL KEBIDANAN, 2017)
Labor pain as a contraction of the myometrium, is a physiological process with a different intensity on each individual. Pain arising in childbirth cause great concern and usually creates fear and stress. Pain management method of the first stage of labor was known two types, it is pharmacological management and non-pharmacological. One way of the non-pharmacological management to decrease the labor pain is endorphine massage. The purpose of this research was to determine the effect of edorphine massage to decrease the pain intensity scale of the first stage of the active phase of labor. This research method usingQuasi experimental designs One Group Pre-test Post-test. The sample in this study were 30 respondents primigravid maternal in the region of Tembarak Temanggung health centers was selected using purposive sampling techniques, and using Wilcoxon test to analysis. In this study 23 respondents showed a better response to a pain scale of the first stage of labor after endorphine massage. While seven other respondents showed no change after being given endorphine massage treatmen. Based on the research results obtained using the Wilcoxon statistical test significance value (p value) of 0.000. It can be concluded that the hypothesis is accepted, there are effect of endorphin massage decline pain intensity scale of the first stage of the active phase of labor. From the results of the study are expected health workers, especially midwives in its role to empower the family in reducing labor pain by conducting socialization in the family and the husband of endorphin massage during a class of pregnant women or antenatal care so that when labor was accompanied by family, especially her husband.